Machiavellianism and learning-related subjective well-being among Chinese senior high school students: A moderated mediation model - Yang, Minqi; Qu, Chunyu; Guo, Hanxiao; Guo, Xicheng; Tian, Kexin; Wang, Guofang (Frontiers in Psychology, 2022)
Based on the life history theory and broadening construction theory, the study aimed to investigate the influence of Machiavellianism on the learning-related subjective well-being and the underlying mechanism, 582 Chinese senior high school students (16.8 ± 0.9 years old) including 289 girls (48.3%) and 310 boys were recruited to participate in this study, and they anonymously filled out questionnaires regarding Machiavellianism, learning-related subjective well-being, gratitude, and subjective family economic level. The results showed that: (1) a higher level of Machiavellianism was associated with a lower level of learning-related subjective well-being; (2) gratitude partially mediated the relationship between Machiavellianism and learning-related subjective well-being; (3) subjective family economic level moderated the links between Machiavellianism and learning-related subjective well-being, and between gratitude and learning-related subjective well-being. This study explained how and when Machiavellianism affected Chinese senior high school students’ learning-related subjective well-being and provided a deeper understanding of the relationship between Machiavellianism and learning-related subjective well-being.